The Migrant Passage : Clandestine Journeys from Central America - Brigden, Noelle (Book collections on Project MUSE., 2018)
"Traces the improvised survival strategies of migrants during their clandestine journeys from Central America and explores the implications of these improvisations for the future of the nation-state"--